XVI Międzynarodowy Kongres Historyków Wychowania w Amsterdamie (10-14.VIIL1994) - Hellwig, Jan (Biuletyn Historii Wychowania, 1995)
XVI Międzynarodowy Kongres Historyków Wychowania w Amsterdamie (10-14.VIIL1994)